An investigation into the components of motivation so far as these determine employee stability and work satisfaction amongst Europeans and Africans engaged in the same occupational grading in the copper mining industry of Zambia - Coetzee, J A G (Rhodes University, Faculty of Humanities, Department of Sociology, 1968)
From introduction: The aim of this study is to analyse the motivational system, so far as this regulates and orients the stability and work satisfactions of Europeans and Africans, in a supervisory occupational category engaged in industrial-mining in the Copper Mining Company of Rhokana, Zambia , during a period of six years, ending in 1963 .
Keywords: Uncatalogued